ANALISIS HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAGING AYAM DI PASAR INDUK KOTA PANGKALPINANG - Dona Pratama Putri; Rahmad Firdaus; Juhari Juhari (JEM Jurnal Ekonomi dan Manajemen, 2022)
This study aims to analyze how much influence the price (X1) and product quality (X2) on the decision to purchase chicken meat at the Main Market of Pangkalpinang City. This research includes causal descriptive research that describes a fact in the field and evaluates the relationship between the variables studied in the form of hypothesis testing. The sample used in this study was 100 respondents. Data analysis method using Multiple Regression Analysis. Hypothesis testing using the F test (simultaneous) and t-test (partial). The results of this study conclude that the two variables price (X1) and product quality (X2) simultaneously have an influence on purchasing decisions for chicken meat at the Pangkalpinang Main Market and partially price and product quality have a significant effect on purchasing decisions.